A Simple and Novel Approach in Treating Congenital Symmastia (Using Tisseel in a 2-Step Approach). (30th September 2020) - Adjei, Bismark; Yao, Susie Z.; Mostafa, Ashraf; Koshy, Ommen
Introduction: Congenital symmastia is notoriously difficult to treat. Many management approaches have been reported but none seem to address the root cause of the anatomic deformity and may result in significant scarring. Method: We propose a minimally invasive approach to treating congenital symmastia with good results and minimal scarring by liposuction and use of a fibrin sealant. Conclusion: Liposuction of the pre-sternal area and injection of fibrin sealant as an adhesive with post-operative pressure garment support worked well to create and maintain a good cleavage.